2015
DOI: 10.1037/a0038730
|View full text |Cite
|
Sign up to set email alerts
|

Unheard voices: African American fathers speak about their parenting practices.

Abstract: Researchers have called for qualitative investigations into African American fathers’ parenting practices that consider their social context and identify specific practices. Such investigations can inform the way we conceptualize African American fathers’ parenting practices, which can in turn contribute to prevention interventions with at-risk youth. We conducted semi-structured, qualitative interviews about parenting with 30 self-identified, African American, biological fathers of pre-adolescent sons at-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 53 publications
8
36
0
Order By: Relevance
“…Paternal caregivers were classified into four classes based on paternal parenting practices that ranged from high to low levels of encouragement and monitoring. These findings are consistent with descriptions of parenting practices in previous literature (Baumrind, , , ; Doyle et al., ; Letiecq & Koblinsky, ; Nebbitt et al., ; Rohner & Khaleque, ; Toth & Xu, ). Moreover, compared to fathers with moderate‐to‐low levels of encouragement and monitoring, caregivers with high levels of encouragement and monitoring were associated with youth who reported less depressive symptoms, higher levels of self‐efficacy, and less favorable attitudes toward deviance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Paternal caregivers were classified into four classes based on paternal parenting practices that ranged from high to low levels of encouragement and monitoring. These findings are consistent with descriptions of parenting practices in previous literature (Baumrind, , , ; Doyle et al., ; Letiecq & Koblinsky, ; Nebbitt et al., ; Rohner & Khaleque, ; Toth & Xu, ). Moreover, compared to fathers with moderate‐to‐low levels of encouragement and monitoring, caregivers with high levels of encouragement and monitoring were associated with youth who reported less depressive symptoms, higher levels of self‐efficacy, and less favorable attitudes toward deviance.…”
Section: Discussionsupporting
confidence: 91%
“…Although sparse, there is some additional evidence that African American fathers in particular engage in the following parenting practices: encouragement (Doyle et al., ; Nebbitt et al., ), psychological control (Bean et al., , ), discipline (Denby & Alford, ; Doyle et al., ; Staples & Johnson, ; Toth & Xu, ), and monitoring (Doyle et al., ; Letiecq & Koblinsky, ; Nebbitt et al., ; Toth & Xu, ). Moreover, some African American fathers may use a parenting style that involves acceptance and increased monitoring (Baumrind, ; Toth & Xu, ).…”
Section: Paternal Caregivers’ Parenting Practices and Youths’ Psycholmentioning
confidence: 99%
“…All fathers in this sample accepted their role to educate their sons about sex. As did those studied by Burns and Caldwell (), fathers in our study also pointed to the significance of a positive father–son relationship as essential to be able to discuss sensitive topics such as sex (Doyle et al, ; Harris et al, ) and promote effective sexual health communication. These fathers reported limited experience in talking about sexual health with their own fathers because their fathers were absent or did not take on the role to educate them about sexual health.…”
Section: Discussionsupporting
confidence: 83%
“…Parent–adolescent closeness or connectedness is a facilitator of sexual health communication (Caldwell, Rafferty, Reischl, DeLoney, & Brooks, ; Doyle et al, ). Harris et al () found that parent–child closeness, defined as the bond a father has with his son, was positively correlated with amount of parent–child sexual communication with both mothers and fathers and with higher condom use self‐efficacy, less permissive sexual attitudes, fewer sexual partners, and fewer incidents of unprotected sex (Harris et al, ).…”
Section: Facilitators and Barriers Of Parent–youth Sexual Health Commmentioning
confidence: 99%
“…Doyle et al . () investigated the parenting styles of thirty Black fathers of pre‐adolescent sons at risk for aggressive behaviours and/or depressive symptoms. Results indicated fathers’ parenting practices were largely influenced by environmental context (i.e.…”
Section: Influences On Black Fathering Practicesmentioning
confidence: 99%